ҚУБЛА АРАЛ БОЙЫ ЭТНОМӘДЕНИЯТЫНЫҢ ДӘСТҮРИЙЛИГИ МӘСЕЛЕСИ - Досмағанбетов, С.; Юсупов, О.; Қайыпназаров, А. (SCIENCE and SOCIETY, 2017)
This article deals with the analysis of the identity of ethno-culture “symbiosis”, ethno-tradition of two ethnoses-Kazakhs and Karakalpaks on the basis of the latest scientific literature in ethnography and ethno-folklore materials. These two, ethnoses have been living for many centuries in the down streams and deltas of Amudarya river, as well as around the Aral sea.
Keywords: ethnoculture; ethnopoem; ethnotraditions; «Korkut ata»; «Koblan»; «Alpamis»; «Er Ziywar»; «Deshti-Kipshak»; migration; material and spiritual culture; around «Miyan kul»